Overcoming the Obstacles of the Ilizarov Device in Extremity Reconstruction: Usefulness of the Perforator as the Recipient Vessel - Kim, Kyu Nam; Hong, Joon Pio; Park, Sung Woo; Kim, Sang Woo; Yoon, Chi Sun (Journal of Reconstructive Microsurgery, 2015)
Background When patients using the Ilizarov device need a free-flap procedure for their thigh and leg, it is difficult to isolate the major vessels as the recipient vessel due to the limited working space around the Ilizarov rings and pins. The usefulness of a perforator as the recipient vessel to allow minimally invasive surgery was investigated in this study.Methods Between October 2011 and December 2013, 77 patients using the Ilizarov device needed free flap reconstruction using an anterolateral thigh perforator flap or superficial circumflex iliac artery perforator flap. The perforator was used as a recipient vessel in 50 cases, with which end-to-end anastomosis was performed using a perforator-to-perforator approach, and major vessels were used as a recipient vessel in 27 cases (n = 20, anterior tibial vessel; n = 7, posterior vessel).Results When the perforator was used as the recipient vessel, total loss developed in one case and marginal necrosis in four cases. When the major vessel was used as the recipient vessel, whole necrosis developed in one case and marginal necrosis in two cases. The procedure increased the freedom of hand movement, decreased the recipient vessel dissection time, and reduced the recipient dissection scar.Conclusions The use of perforators as recipients overcomes the obstacles associated with the Ilizarov device and allows convenient and rapid reconstruction, with similar success as microsurgery using major vessels. Further studies are needed to address the limitations of this approach, which include perfusion physiology and the viable limit of the flap dimension.
Keywords: Ilizarov device; supermicrosurgery; perforator-to-perforator anastomosis